2019
DOI: 10.1177/1555412019866348
|View full text |Cite|
|
Sign up to set email alerts
|

Balancing Gender Identity and Gamer Identity: Gender Issues Faced by Wang ‘BaiZe’ Xinyu at the 2017 Hearthstone Summer Championship

Abstract: This article examines a terrain in which gender inclusion remains a challenge: competitive esports. In the male-dominated sphere of esports, the underrepresentation of women and nonbinary people often leaves these marginalized groups invisible, with a significant lack of women and nonbinary people competing in top-tier tournaments. We highlight the experience of Wang ‘BaiZe’ Xinyu, a Chinese Hearthstone player who became the first woman to compete in a Hearthstone Championship Tour event in the game’s 3-year h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…These behaviors, in the enaction of a hybrid masculinity for analog gamers, asserts gaming occurs in a male space. “The construction of a masculinized culture has also helped reinforce masculine behavior between male members of the community in which they participate” (Schelfhout et al, 2021, p. 27).…”
Section: Masculinity and Male Preservesmentioning
confidence: 99%
“…These behaviors, in the enaction of a hybrid masculinity for analog gamers, asserts gaming occurs in a male space. “The construction of a masculinized culture has also helped reinforce masculine behavior between male members of the community in which they participate” (Schelfhout et al, 2021, p. 27).…”
Section: Masculinity and Male Preservesmentioning
confidence: 99%
“…Studi tentaang game sebelumnya telah banyak dilakukan, misalnya motivasi pemain game (Lee & Kim, 2016), pengaruh video game terhadap kehidupan sosial para pemain game (Grove & Looy, 2015), dan representasi gender dalam video game (Schelfhout, Bowers, & Hao, 2019). Namun, ada satu topik menarik dan perlu dikaji secara mendalam yaitu tentang konstruksi identitas gamer Muslimah dalam dunia virtual game daring.…”
Section: Pendahuluanunclassified
“…The traditional “gamer” stereotype and its associated characteristics have influenced external perceptions of gaming as well as the internal dynamics which develop and reinforce gaming culture. The traditionally male perception of a “gamer” has led to accusations that gaming culture exhibits hegemonic masculinity (Schelfhout et al, 2019). This hegemony is said to be reinforced within the gaming culture in multiple ways.…”
Section: Introductionmentioning
confidence: 99%
“…The communities formed from the growth of the video game industry represent an increasingly acceptable form of social engagement. Research has shown that digital gaming offers a number of positive social, vocational, and educational rewards (Schelfhout, Bowers, & Hao, 2019). Despite the growing acceptance of gaming as a recreational, creative, and social medium, popular perceptions of the gaming audience have been slower to evolve.…”
mentioning
confidence: 99%
See 1 more Smart Citation